Land Politics and Food Security: A New Perspective on Land Degradation in Indonesia - Hajad, Vellayati; Handayani, Sri Wahyu; Ikhsan, Ikhsan; Setiawan, Deni; Fadhly, Zuhrizal; Herizal, Herizal (SCAD Independent, 2025)
Land degradation has emerged as a critical global issue, with significant implications for food security, agricultural productivity, and environmental sustainability. In Indonesia, this problem is deeply intertwined with land politics, where land ownership and access inequities exacerbate the challenges posed by soil erosion, unsustainable agricultural practices, and socio-economic transitions. This study examines the relationship between land degradation and food security, focusing on how agrarian politics influence these dynamics. Through a qualitative approach systematic literature review, we analyzed articles from the Scopus database using VOSviewer to identify critical patterns and themes. The findings highlight that dryland farming areas in Indonesia are particularly vulnerable, with land degradation being aggravated by urbanization, economic pressures, and socio-political factors such as unequal land ownership and inadequate policy implementation. While agrarian reform initiatives have been proposed to address disparities in land access and improve resource distribution, their effectiveness remains limited due to insufficient community involvement and a lack of integration between local socio-ecological knowledge and policy frameworks. This research underscores the need for a comprehensive approach to land management that integrates equitable land policies, community participation, and sustainable agricultural practices. By addressing the socio-political dimensions of land use and degradation, Indonesia can enhance food security and create a more resilient agricultural sector.